Swedish Version of the System Usability Scale: Translation, Adaption, and Psychometric Evaluation - Helene Åvik Persson; Charlotte Castor; Nilla Andersson; Mia Hylén (JMIR Human Factors)
Abstract BackgroundThe Swedish health care system is undergoing a transformation. eHealth technologies are increasingly being used. The System Usability Scale is a widely used tool, offering a standardized and reliable measure for assessing the usability of digital health solutions. However, despite the existence of several translations of the System Usability Scale into Swedish, none have undergone psychometric validation. This highlights the urgent need for a validated and standardized Swedish version of the System Usability Scale to ensure accurate and reliable usability evaluations. ObjectiveThe aim of the study was to translate and psychometrically evaluate a Swedish version of the System Usability Scale. MethodsThe study utilized a 2-phase design. The first phase translated the System Usability Scale into Swedish and the second phase tested the scale’s psychometric properties. A total of 62 participants generated a total of 82 measurements. Descriptive statistics were used to visualize participants’ characteristics. The psychometric evaluation consisted of data quality, scaling assumptions, and acceptability. Construct validity was evaluated by convergent validity, and reliability was evaluated by internal consistency. ResultsThe Swedish version of the System Usability Scale demonstrated high conformity with the original version. The scale showed high internal consistency with a Cronbach α of .852 and corrected item-total correlations ranging from 0.454 to 0.731. The construct validity was supported by a significant positive correlation between the System Usability Scale and domain 5 of the eHealth Literacy Questionnaire (P ConclusionsThe Swedish version of the System Usability Scale demonstrated satisfactory psychometric properties. It can be recommended for use in a Swedish context. The positive correlation with domain 5 of the eHealth Literacy Questionnaire further supports the construct validity of the Swedish version of the System Usability Scale, affirming its suitability for evaluating digital health solutions. Additional tests of the Swedish version of the System Usability Scale, for example, in the evaluation of more complex eHealth technology, would further validate the scale.